Health economics - Street, Andrew (Cambridge University Press, 2023)
This Element examines economic perspectives on improving quality and safety in healthcare. Though competition is generally recognised by economists as an important driver of improvement, it may not work so straightforwardly in healthcare - in part because some services are provided by very few organisations, but also because people are not always easily able to judge healthcare quality and rarely have to pay the full price for services. Different approaches for stimulating improvement are therefore needed, and the authors look at examples from the care home, primary care, and hospital sectors. They emphasise the need for economic evaluation of improvement efforts, based on the principle that improvement activities should only be undertaken if the benefits are worth at least the costs of implementing and running them. Using examples, they explain the economic approach to evaluating how benefits and costs of improvement efforts can be compared by applying cost-effectiveness analysis. This title is also available as Open Access on Cambridge Core.